2013
DOI: 10.1371/journal.pone.0071541
|View full text |Cite
|
Sign up to set email alerts
|

HDL-apoA-I Exchange: Rapid Detection and Association with Atherosclerosis

Abstract: High density lipoprotein (HDL) cholesterol levels are associated with decreased risk of cardiovascular disease, but not all HDL are functionally equivalent. A primary determinant of HDL functional status is the conformational adaptability of its main protein component, apoA-I, an exchangeable apolipoprotein. Chemical modification of apoA-I, as may occur under conditions of inflammation or diabetes, can severely impair HDL function and is associated with the presence of cardiovascular disease. Chemical modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(131 citation statements)
references
References 84 publications
(104 reference statements)
6
125
0
Order By: Relevance
“…However, factors controlling HDL sterol effl ux capacity are largely unknown. Our previous work indicated that the ability of HDL to remodel and/or exchange apoA-I is attenuated in CVD subjects with similar apoA-I and HDL-C levels, suggesting that direct measurement of HDL dynamics measures a HDL property distinct from apoA-I or cholesterol concentration ( 31 ). To establish whether HAE and cholesterol effl ux capacity assays measure independent HDL properties, we investigated the relationship between HDL dynamics, as measured by the HAE assay, and cholesterol effl ux capacity, as measured by the cell-based assays.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, factors controlling HDL sterol effl ux capacity are largely unknown. Our previous work indicated that the ability of HDL to remodel and/or exchange apoA-I is attenuated in CVD subjects with similar apoA-I and HDL-C levels, suggesting that direct measurement of HDL dynamics measures a HDL property distinct from apoA-I or cholesterol concentration ( 31 ). To establish whether HAE and cholesterol effl ux capacity assays measure independent HDL properties, we investigated the relationship between HDL dynamics, as measured by the HAE assay, and cholesterol effl ux capacity, as measured by the cell-based assays.…”
Section: Discussionmentioning
confidence: 99%
“…HAE assay methods were performed with apoB-depleted plasma as described in Borja, et al ( 31 ), except that the EPR spectrum collection at 6°C was omitted, as analysis of previous data revealed the assay gave the same results when this step was not performed. Spin labeling of apoA-I is described in Oda et al ( 32 ).…”
Section: Hae Assaymentioning
confidence: 99%
See 3 more Smart Citations